Intellectual property law in Switzerland - Dessemontet, François (Kluwer Law International, 2019)
Derived from the renowned multi-volume 'International Encyclopaedia of Laws', this monograph provides a survey and analysis of the rules concerning intellectual property rights in the Switzerland. It covers every type of intellectual property right in depth? copyright and neighbouring rights, patents, utility models, trademarks, trade names, industrial designs, plant variety protection, chip protection, trade secrets, and confidential information. Particular attention is paid throughout to recent developments and trends.00The analysis approaches each right in terms of its sources in law and in legislation, and proceeds to such legal issues as subject matter of protection, conditions of protection, ownership, transfer of rights, licences, scope of exclusive rights, limitations, exemptions, duration of protection, infringement, available remedies, and overlapping with other intellectual property rights.